Effect of organic manures and biofertilizers on yield, dry matter partitioning and quality traits of cabbage (Brassica oleracea var. capitata) - UPADHYAY, A K; BAHADUR, ANANT; SINGH, JAGDISH (The Indian Journal of Agricultural Sciences, 2012)
The objective of this study was to evaluate the effects of three different biofertilizers in combination with four different organic manures or with inorganic fertilizers on dry matter partitioning, yield and quality traits in cabbage. Results indicated that treatments comprising recommended fertilizers package coupled with seedling inoculation in any biofertilizer had relatively higher dry matter in leaves (head), higher number of non-wrapper leaves and head yield (40.81– 41.88±1.07 tonnes/ha). Application of pressmud or vermicompost plus seedling inoculation in Azospirillum or PSM noticed head yield at par with conventional fertilization. The total carbohydrate content in head was significantly higher with use of organic manures and VAM or PSM. The maximum protein content was noticed with sole application of vermicompost (17.4%) or digested sludge (17.3%). Fibre content in head was improved remarkably with the use of organic manures and biofertilizers. The highest total carotenoid content in head was recorded with the use of FYM + PSM (0.445 mg/100 g). Significantly higher ascorbic acid content (vitamin C) in head was registered with the use of either FYM or pressmud along with PSM or VAM (14.25–15.48±0.33 mg/100 g).